Upaya Preventif Pertama pada Emesis Gravidarum dengan Pembudidayaan Tanaman Jahe Merah di Kelompok Wanita Tani Sri Mandiri Sindangkasih - Asmarani, Sri Utami; Sandriani, Sandriani; Yusuf, Anna L; Purwati, Ayu Endang (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Pregnancy is a condition that requires psychological and physiological adaptation to the influence of pregnancy hormones and mechanical stress due to the enlargement of the uterus and other tissues. Pregnant women will experience changes that make them uncomfortable, one of which is emesis gravidarum. The complaint of nausea and vomiting in emesis gravidarum is physiological, but if this complaint is not resolved immediately, it will become pathological. Objective: This community service was carried out to increase the knowledge and skills of the KWT Sri Mandiri in the cultivation of red ginger and the use of ginger plants as a non-pharmacological therapy for the initial treatment of emesis gravidarum. Method: The method used in this community service involves 3 phases of activity, namely preparation, implementation and evaluation. Result: The results of the community service activities carried out at the Sri Mandiri Sindangkasih Women Farmers Group (KWT) showed that there was an increase in the knowledge and skills of the Sri Mandiri Women Farmers Group (KWT) on red ginger cultivation and the use of ginger plants as a non-pharmacological therapy for the first treatment of emesis gravidarum. Conclusion: The conclusion from the implementation of this community service is that all stages of activities on red ginger cultivation and use of ginger plants to reduce emesis gravidarum can be carried out well supported by the enthusiasm of KWT Sri Mandiri.